Sinister Wisdom : a journal of words and pictures for the lesbian imagination in all women (Lincoln: Sinister Wisdom)
"Fonds Suzan Daniel (FSD)Periodiciteit : driemaandelijksRedactie : Box 30541, Lincoln, Nebraska 68503, vanaf (1980) 15 ; PO Box 660, Amherst, MA 01004"